Health factors and academic performance among residential college students - Ruzita Abd. Talib; Zuriana Fahila Kahairudin; Roslee Rajikan; Noor Alaudin Abd Wahab (Pusat Perkembangan Pelajar ,U.K.M, 2013)
A healthy lifestyle is very important to ensure a good health during study period at university This study aims to measure the body mass index (BMI), physical activities, sleep duration and academic performance among 334 Universiti Kebangsaan Malaysia students staying in Tun Syed Nasir Residential College, Kuala Lumpur All data were collected using questionnaires and anthropometric measurement. The results showed 22% of students had underweight problems, 11% overweight and 3% obese, respectively About half of the male students (52%) showed high physical activity levels, whereas moderate physical activity levels were reported in 59% offemale students. Additionally, majority of the students (90%) had sleep duration less than eight hours per day The participated students showed 3.06±0.34 of min CGPA. Pearson correlation test showed in-significant relationship between moderate physical activity walking and sleep duration during weekends with CGPA performance. However there were negative relationship between BMI (r=-0. 174, p<0.05) and high physical activities (r= -0.118, p< 0.05) with CGPA performance. Moreover, only sleep duration were found to have significant positive correlation with CGPA performance (r=0.132, p<0.05). In conclusion, this study manages to prove that students 'academic performance is related to BM1, physical activities and sleep duration.